PENGARUH ECONOMIC LITERACY, PENGGUNAAN UANG ELEKTRONIK, DAN LIFESTYLE TERHADAP PERILAKU KONSUMTIF MASYARAKAT INDONESIA (KASUS ANGGOTA KELOMPOK BERBURUSALE PADA TELEGRAM) - Tanti Rahmawati; Siti Nurjanah; Rd. Tuty Sariwulan (Transpublika Publisher, 2023)
This study aims to analyze the influence of economic literacy, use of electronic money and lifestyle on consumptive behavior. The method used in this research is a quantitative method. The population in this study are members of the Berburusale group who are on the Telegram application with a sample of 347 members of the Berburusale group. Sampling technique with Proportional Random Sampling. Data collection was carried out by distributing questionnaires to 347 members of the Berburusale group. The data analysis technique used is the chi-square test and Spearman's rank correlation. The results of this study are: 1) Economic literacy has a negative and significant effect of 15.9% on consumptive behavior, 2) The use of electronic money has a positive and significant effect of 21.6% on consumptive behavior, 3) Lifestyle has a positive and significant effect by 45% on consumptive behavior.